Impact of Interface Traps on Direct and Alternating Current in Tunneling Field-Effect Transistors - Zhi Jiang; Yiqi Zhuang; Cong Li; Ping Wang; Yuqi Liu (Journal of Electrical and Computer Engineering)
We demonstrate the impact of semiconductor/oxide interface traps (ITs) on the DC and AC characteristics of tunnel field-effect transistors (TFETs). Using the Sentaurus simulation tools, we show the impacts of trap density distribution and trap type on the n-type double gate- (DG-) TFET. The results show that the donor-type and acceptor-type ITs have the great influence on DC characteristic at midgap. Donor-like and acceptor-like ITs have different mechanism of the turn-on characteristics. The flat band shift changes obviously and differently in the AC analysis, which results in contrast of peak shift of Miller capacitor Cgd for n-type TFETs with donor-like and acceptor-like ITs.